Cloud computing as a key enabler for digital government across Asia and the Pacific - Abell, Thomas; Husar, Arndt; Lim, May-Ann (Sustainable development working papers., 2021)
Many egovernment capabilities, digital tools and services, data analytics, and digital economy development plans are enabled by cloud computing technologies. In this paper, the authors emphasize the rapidly scalable computing resources that cloud computing delivers via the internet and its potential to significantly improve the efficiency of government services.